Long-Term Forest Dynamics and Land-Use Abandonment in the Mediterranean Mountains, Corsica, France - Sanz, Almudena San Roman; Fernandez, Catherine; Mouillot, Florent; Ferrat, Lila; Istria, Daniel; Pasqualini, Vanina (ECOLOGY AND SOCIETY, 2013)
Human practices have had an impact on Mediterranean ecosystems for millennia, particularly through agricultural and pastoral activities. Since the mid-19th century, land-use abandonment has led to the expansion of shrubland and forest, especially in the mountainous areas of the northern Mediterranean basin. Knowledge of these factors is vital to understanding present forest patterns and predicting future forest dynamics in the Mediterranean mountains. We aimed to analyze and understand how land-use abandonment affected spatial modifications of landscapes in two study areas, 44,000 ha and 60,000 ha, located on the island of Corsica, France, representing a typical Mediterranean environment with chestnut forests. Our approach used land-cover archive documents from 1774, 1913, 1975, and 2000, and human population history, 1770 to present day, to describe landscape patterns following land-use abandonment. This research showed that dramatic changes in landscape at the two study areas were caused by the suspension of human influence and the interruption of traditional farming practices. Over the study period, both study sites showed significant reforestation of shrubland and cultivated areas marked by the presence of Quercus ilex forests (+3.40% yr-1 between 1975 and 2000) and by Pinus pinaster (+3.00% yr-1 between 1975 and 2000) at one study site that had experienced heavy rural exodus. At the same time, areas containing chestnut forests decreased by 50% between 1774 and 2000 (-0.09% yr-1 between 1774 and 1975 and -1.42% yr-1 between 1975 and 2000). Shrubland expansion remained limited at both study sites. Our study highlights the value of small-scale approaches for understanding the ecological consequences of land-use abandonment and present and future land-management decisions. Discussion concludes on the importance of working with long-term series for studies on resilience in social-ecological systems and on the consequences in terms of provision of ecosystem services.
Keywords: historical archives; human population; Land-use change; landscape patterns; Mediterranean ecosystems